High-strength tear-resistant EPE composite material and preparation method thereof
By combining modified polyethylene resin and polyalkenes, combined with carbon fiber and nanotitanium dioxide, the problem of insufficient mechanical strength and tear resistance of EPE materials is solved, and the comprehensive performance and anti-aging properties of the material are significantly improved.
Patent Information
- Application Number
- CN202411701775.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing EPE materials have low mechanical strength and tear resistance, making it difficult to meet the industry's demand for higher physical properties.
Modified polyethylene resin and polyaldehyde are combined and modified by silane coupling agent KH560, combining carbon fiber composite material and nanotitanium dioxide to improve the mechanical properties and anti-aging properties of the material.
It significantly improves the mechanical properties and tear resistance of the composite material, while improving the flexibility and impact resistance of the material, enhancing the bonding force with the filler and anti-aging properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foaming materials, and in particular to a high-strength tear-resistant EPE composite material and a preparation method thereof. Background Art
[0002] EPE (expandable polyethylene), also known as pearl cotton, is a high-foam polyethylene material with a non-cross-linked closed-cell structure. It is mainly made of low-density polyethylene (LDPE) as raw material and is extruded through a physical foaming process to form a lightweight, flexible foam material with excellent cushioning properties. EPE usually has a low density, which allows it to effectively reduce the overall weight and transportation costs when packaging and protecting products.
[0003] EPE is widely used in many industries, especially in the inner packaging of electronic appliances, instruments and meters, medical devices, lighting, handicrafts, glass products, home appliances, fruits and other products. Its non-toxic and environmentally friendly characteristics make EPE an ideal choice for food packaging and medical device packaging, meeting the safety and environmental protection requirements of modern consumers.
[0004] Since EPE is mainly made from low-density polyethylene (LDPE) through a physical foaming process, and LDPE itself has low mechanical strength, the EPE material alone exhibits brittle and easy-to-break characteristics in terms of physical properties. Therefore, improving the mechanical strength and tear strength of EPE materials has become an important issue that needs to be urgently addressed in the industry. For example, Chinese patent document CN201810130489.2 discloses a tear-resistant EPE and a preparation method thereof, comprising 70-80 parts of a base material, 10-20 parts of a foaming agent, 3-7 parts of a nucleating agent, 1-2 parts of an anti-shrinkage agent, 1-3 parts of an antistatic agent, and 1-2 parts of a performance-improving agent, wherein the base material comprises LDPE, LLDPE, and ULDPE, and the performance-improving agent comprises polypropylene fiber, glass fiber, and silicone flame retardant. Although the mechanical properties of the prepared EPE material have been improved to a certain extent, further improvement is still required. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-strength tear-resistant EPE composite material and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical scheme: A high-strength tear-resistant EPE composite material comprises the following raw materials in parts by weight: 80-100 parts of modified polyethylene resin, 20-30 parts of polycaprolactone, 15-25 parts of foaming agent, 10-20 parts of carbon fiber composite material, 1-3 parts of zinc stearate and 1-2 parts of antioxidant.
[0007] In some embodiments of the present invention, the modified polyethylene resin can be selected from 80 parts, 82 parts, 84 parts, 85 parts, 88 parts, 90 parts, 92 parts, 95 parts, 98 parts, and 100 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0008] Specifically, the preparation method of the modified polyethylene resin is as follows: polyethylene resin and silane coupling agent KH560 are uniformly mixed, and the mixture is melt-extruded by a screw to obtain the modified polyethylene resin.
[0009] More specifically, the mass ratio of polyethylene resin to silane coupling agent KH560 is 100:3-5, for example, 100:3, 100:4, 100:5 can be selected, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0010] More specifically, the temperature of the screw melt extrusion process is 180-210° C., and the screw speed is controlled at 90-100 r / min.
[0011] In some embodiments of the present invention, the polycaprolactone can be selected from 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, and 30 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0012] In some embodiments of the present invention, the foaming agent can be selected from 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, and 25 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] Specifically, the blowing agent is selected from butane.
[0014] In some embodiments of the present invention, the carbon fiber composite material can be selected from 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, and 20 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0015] Specifically, the preparation method of the carbon fiber composite material is as follows: S1, dispersing carbon fiber in an ethanol aqueous solution, then adding diallyldiethoxysilane thereto, stirring for 1-3 hours, then filtering, washing, and drying to obtain pretreated carbon fiber; S2, dispersing the pretreated carbon fiber in deionized water, then adding p-hydroxycinnamic acid and initiator persulfate thereto, heating and stirring to react, and after the reaction is completed, filtering, washing, and drying to obtain modified carbon fiber; S3, dispersing the modified carbon fiber in an ethanol solvent, then adding deionized water, ammonia water and tetrabutyl titanate thereto, stirring for 6-12 hours, and after the reaction is completed, filtering, washing and drying to obtain a carbon fiber composite material.
[0016] More specifically, in step S1, the mass ratio of carbon fiber to diallyldiethoxysilane is 10-15:1-2, for example, 10:1, 10:2, 12:1, 12:2, 15:1, 15:2 can be selected, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] More specifically, in step S2, the mass ratio of the pretreated carbon fiber, p-hydroxycinnamic acid and persulfate is 10-15:4-8:0.5-1.
[0018] Wherein, the persulfate is selected from sodium persulfate, potassium persulfate or ammonium persulfate.
[0019] More specifically, in step S2, the temperature of the heating and stirring reaction is 60-80°C, for example, 60°C, 65°C, 70°C, 75°C, and 80°C can be selected; the time of the heating and stirring reaction is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, and 4h can be selected, but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] More specifically, in step S3, the mass ratio of the modified carbon fiber, ethanol, deionized water, ammonia water and tetrabutyl titanate is 5-10:150:5-10:10-15:10-20.
[0021] In some embodiments of the present invention, the zinc stearate can be selected to be 1 part, 1.5 parts, 2 parts, 2.5 parts, or 3 parts, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] In some embodiments of the present invention, the antioxidant may be selected to be 1 part, 1.5 parts, or 2 parts, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Specifically, the antioxidant is selected from antioxidant 1010.
[0024] The present invention also provides a method for preparing the above-mentioned high-strength and tear-resistant EPE composite material, comprising the following steps: adding modified polyethylene resin, polycaprolactone and carbon fiber composite material into a foaming extruder according to weight, melt blending to obtain a mixed material, then adding a foaming agent, zinc stearate and an antioxidant, foaming for 15-20 minutes under the conditions of a temperature of 180-200°C and an inlet pressure of 8-12MPa, and cooling after the foaming is completed to obtain a high-strength and tear-resistant EPE composite material.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) Since polyethylene resin has the performance characteristics of low mechanical strength and low tear strength, the present invention adopts modified polyethylene resin and polycaprolactone for compounding, which can improve the overall mechanical properties of the composite material, so that when it is subjected to external force, it can maintain good flexibility and have certain tear resistance and impact resistance.
[0026] (2) The present invention uses silane coupling agent KH560 to modify the polyethylene resin, introduces epoxy groups on the surface of the polyethylene resin, improves the bonding force between the polyethylene resin and other fillers, and thus improves the mechanical properties of the composite material.
[0027] (3) The present invention first uses diallyldiethoxysilane to pretreat the carbon fiber, introduces carbon-carbon double bonds on the surface of the carbon fiber, and then grafts p-hydroxycinnamic acid on the surface of the pretreated carbon fiber through an addition reaction between the double bonds to obtain modified carbon fiber, and then deposits nano-titanium dioxide on the surface of the modified carbon fiber to obtain a carbon fiber composite material; p-hydroxycinnamic acid contains hydroxyl groups, carboxyl groups and the like, which can react chemically with the epoxy groups in the modified polyethylene resin, thereby enhancing the bonding force between the polyethylene resin and the carbon fiber composite material, and further improving the mechanical properties of the composite material; at the same time, the nano-titanium dioxide on the surface of the carbon fiber composite material can provide a heterogeneous nucleation effect during the foaming process. Compared with directly blending carbon fiber and nano-titanium dioxide, the nano-titanium dioxide in the present invention is more evenly dispersed, forming a nano-enhancement effect, and the comprehensive performance of the composite material is more significantly improved; in addition, p-hydroxycinnamic acid contains a rigid benzene ring structure, which works together with nano-titanium dioxide to improve the anti-aging performance of the EPE composite material. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0029] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0030] The polyethylene resin used in the present invention is a low-density polyethylene resin, model 2102TX00, purchased from Shanghai Bangsu New Materials Co., Ltd.; polycaprolactone is purchased from Shanghai Yiding Plastic Co., Ltd.; the carbon fiber is chopped carbon fiber, with a length of 1-3 mm, purchased from Nantong Woyuan New Materials Technology Co., Ltd. Example 1
[0031] A method for preparing a high-strength tear-resistant EPE composite material comprises the following steps: 85 parts of modified polyethylene resin, 25 parts of polycaprolactone and 15 parts of carbon fiber composite material are added to a foaming extruder, melt blended to obtain a mixed material, and then 20 parts of foaming agent butane, 2 parts of zinc stearate and 1 part of antioxidant 1010 are added, and foaming is carried out for 15 minutes at a temperature of 180°C and an inlet pressure of 10MPa. After the foaming is completed, it is cooled to obtain a high-strength and tear-resistant EPE composite material.
[0032] The preparation method of the modified polyethylene resin is as follows: 100 parts of polyethylene resin and 3 parts of silane coupling agent KH560 are mixed evenly, and the mixture is processed by screw melt extrusion. The temperature of the screw melt extrusion is 180°C, and the screw speed is controlled at 100r / min to obtain the modified polyethylene resin.
[0033] The preparation method of carbon fiber composite material is as follows: S1, dispersing 10 g of carbon fiber in 100 mL of 80 wt% ethanol aqueous solution, then adding 1 g of diallyldiethoxysilane thereto, stirring for 2 h, then filtering, washing, and drying to obtain pretreated carbon fiber; S2, 10g of pretreated carbon fiber was dispersed in 150mL of deionized water, and then 4g of p-hydroxycinnamic acid and 0.5g of initiator ammonium persulfate were added thereto, and the mixture was heated and stirred at 60°C for 4h. After the reaction was completed, the modified carbon fiber was obtained by filtering, washing and drying; S3. Disperse 5 g of modified carbon fiber in 150 g of ethanol solvent, then add 5 g of deionized water, 10 g of 25 wt% ammonia water and 10 g of tetrabutyl titanate, stir for 8 h, and after the reaction is completed, filter, wash and dry to obtain a carbon fiber composite material. Example 2
[0034] A method for preparing a high-strength tear-resistant EPE composite material comprises the following steps: 80 parts of modified polyethylene resin, 20 parts of polycaprolactone and 10 parts of carbon fiber composite materials are added to a foaming extruder, melt blended to obtain a mixed material, and then 15 parts of foaming agent butane, 1 part of zinc stearate and 1 part of antioxidant 1010 are added, and foaming is carried out for 15 minutes at a temperature of 180°C and an inlet pressure of 10MPa. After the foaming is completed, it is cooled to obtain a high-strength and tear-resistant EPE composite material.
[0035] The preparation method of the modified polyethylene resin is as follows: 100 parts of polyethylene resin and 5 parts of silane coupling agent KH560 are mixed evenly, and the mixture is processed by screw melt extrusion. The temperature of the screw melt extrusion is 180°C, and the screw speed is controlled at 100r / min to obtain the modified polyethylene resin.
[0036] The preparation method of carbon fiber composite material is as follows: S1, dispersing 15g of carbon fiber in 100mL of 80wt% ethanol aqueous solution, then adding 2g of diallyldiethoxysilane thereto, stirring for 2h, then filtering, washing and drying to obtain pretreated carbon fiber; S2, 15g of pretreated carbon fiber was dispersed in 150mL of deionized water, and then 8g of p-hydroxycinnamic acid and 1g of initiator ammonium persulfate were added thereto, and the mixture was heated and stirred at 80°C for 2h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified carbon fiber; S3. Disperse 10 g of modified carbon fiber in 150 g of ethanol solvent, then add 10 g of deionized water, 15 g of 25 wt% ammonia water and 20 g of tetrabutyl titanate, stir for 6 hours, and after the reaction is completed, filter, wash and dry to obtain a carbon fiber composite material. Example 3
[0037] A method for preparing a high-strength tear-resistant EPE composite material comprises the following steps: 100 parts of modified polyethylene resin, 30 parts of polycaprolactone and 20 parts of carbon fiber composite material are added to a foaming extruder, melt blended to obtain a mixed material, and then 25 parts of foaming agent butane, 3 parts of zinc stearate and 2 parts of antioxidant 1010 are added, and foaming is carried out for 15 minutes at a temperature of 200°C and an inlet pressure of 12 MPa. After the foaming is completed, it is cooled to obtain a high-strength and tear-resistant EPE composite material.
[0038] The preparation method of the modified polyethylene resin is as follows: 100 parts of polyethylene resin and 4 parts of silane coupling agent KH560 are mixed evenly, and the mixture is processed by screw melt extrusion. The temperature of the screw melt extrusion is 180°C, and the screw speed is controlled at 100r / min to obtain the modified polyethylene resin.
[0039] The preparation method of carbon fiber composite material is as follows: S1, dispersing 12 g of carbon fiber in 100 mL of 80 wt% ethanol aqueous solution, then adding 1.5 g of diallyldiethoxysilane thereto, stirring for 3 h, then filtering, washing, and drying to obtain pretreated carbon fiber; S2, 12g of pretreated carbon fiber was dispersed in 150mL of deionized water, and then 6g of p-hydroxycinnamic acid and 0.8g of initiator ammonium persulfate were added thereto, and the mixture was heated and stirred at 80°C for 2h. After the reaction was completed, the mixture was filtered, washed and dried to obtain modified carbon fiber; S3. Disperse 8 g of modified carbon fiber in 150 g of ethanol solvent, then add 10 g of deionized water, 15 g of 25 wt% ammonia water and 15 g of tetrabutyl titanate, stir for 12 h, and after the reaction is completed, filter, wash and dry to obtain a carbon fiber composite material. Comparative Example 1
[0040] A method for preparing a high-strength tear-resistant EPE composite material comprises the following steps: 85 parts of modified polyethylene resin and 15 parts of carbon fiber composite material are added to a foaming extruder, melt blended to obtain a mixed material, and then 20 parts of foaming agent butane, 2 parts of zinc stearate and 1 part of antioxidant 1010 are added, and foaming is carried out for 15 minutes at a temperature of 180°C and an inlet pressure of 10MPa. After the foaming is completed, it is cooled to obtain a high-strength and tear-resistant EPE composite material.
[0041] The preparation method of the modified polyethylene resin is as follows: 100 parts of polyethylene resin and 3 parts of silane coupling agent KH560 are mixed evenly, and the mixture is processed by screw melt extrusion. The temperature of the screw melt extrusion is 180°C, and the screw speed is controlled at 100r / min to obtain the modified polyethylene resin.
[0042] The preparation method of carbon fiber composite material is as follows: S1, dispersing 10 g of carbon fiber in 100 mL of 80 wt% ethanol aqueous solution, then adding 1 g of diallyldiethoxysilane thereto, stirring for 2 h, then filtering, washing, and drying to obtain pretreated carbon fiber; S2, 10g of pretreated carbon fiber was dispersed in 150mL of deionized water, and then 4g of p-hydroxycinnamic acid and 0.5g of initiator ammonium persulfate were added thereto, and the mixture was heated and stirred at 60°C for 4h. After the reaction was completed, the modified carbon fiber was obtained by filtering, washing and drying; S3. Disperse 5 g of modified carbon fiber in 150 g of ethanol solvent, then add 5 g of deionized water, 10 g of 25 wt% ammonia water and 10 g of tetrabutyl titanate, stir for 8 h, and after the reaction is completed, filter, wash and dry to obtain a carbon fiber composite material.
[0043] Compared with Example 1, Comparative Example 1 does not add polycaprolactone. Comparative Example 2
[0044] A method for preparing a high-strength tear-resistant EPE composite material comprises the following steps: 85 parts of polyethylene resin, 25 parts of polycaprolactone and 15 parts of carbon fiber composite material are added to a foaming extruder, melt blended to obtain a mixed material, and then 20 parts of foaming agent butane, 2 parts of zinc stearate and 1 part of antioxidant 1010 are added, and foaming is carried out for 15 minutes at a temperature of 180°C and an inlet pressure of 10MPa. After the foaming is completed, it is cooled to obtain a high-strength and tear-resistant EPE composite material.
[0045] The preparation method of the carbon fiber composite material is as follows: S1, dispersing 10 g of carbon fiber in 100 mL of 80 wt% ethanol aqueous solution, then adding 1 g of diallyldiethoxysilane thereto, stirring for 2 h, then filtering, washing, and drying to obtain pretreated carbon fiber; S2, 10g of pretreated carbon fiber was dispersed in 150mL of deionized water, and then 4g of p-hydroxycinnamic acid and 0.5g of initiator ammonium persulfate were added thereto, and the mixture was heated and stirred at 60°C for 4h. After the reaction was completed, the modified carbon fiber was obtained by filtering, washing and drying; S3. Disperse 5 g of modified carbon fiber in 150 g of ethanol solvent, then add 5 g of deionized water, 10 g of 25 wt% ammonia water and 10 g of tetrabutyl titanate, stir for 8 h, and after the reaction is completed, filter, wash and dry to obtain a carbon fiber composite material.
[0046] Compared with Example 1, Comparative Example 2 did not perform modification treatment on the polyethylene resin. Comparative Example 3
[0047] A method for preparing a high-strength tear-resistant EPE composite material comprises the following steps: 85 parts of modified polyethylene resin, 25 parts of polycaprolactone and 15 parts of carbon fiber are added to a foaming extruder, melt blended to obtain a mixed material, and then 20 parts of foaming agent butane, 2 parts of zinc stearate and 1 part of antioxidant 1010 are added. The mixture is foamed for 15 minutes at a temperature of 180°C and an inlet pressure of 10 MPa. After the foaming is completed, the mixture is cooled to obtain a high-strength and tear-resistant EPE composite material.
[0048] The preparation method of the modified polyethylene resin is as follows: 100 parts of polyethylene resin and 3 parts of silane coupling agent KH560 are mixed evenly, and the mixture is processed by screw melt extrusion. The temperature of the screw melt extrusion is 180°C, and the screw speed is controlled at 100r / min to obtain the modified polyethylene resin.
[0049] Compared with Example 1, Comparative Example 3 did not perform modification treatment on the carbon fiber. Comparative Example 4
[0050] A method for preparing a high-strength tear-resistant EPE composite material comprises the following steps: 85 parts of modified polyethylene resin, 25 parts of polycaprolactone, 10 parts of carbon fiber and 5 parts of nano titanium dioxide (particle size 60nm) were added to a foaming extruder and melt-blended to obtain a mixed material. Subsequently, 20 parts of foaming agent butane, 2 parts of zinc stearate and 1 part of antioxidant 1010 were added and foamed for 15 minutes at a temperature of 180°C and an inlet pressure of 10MPa. After the foaming was completed, it was cooled to obtain a high-strength and tear-resistant EPE composite material.
[0051] The preparation method of the modified polyethylene resin is as follows: 100 parts of polyethylene resin and 3 parts of silane coupling agent KH560 are mixed evenly, and the mixture is processed by screw melt extrusion. The temperature of the screw melt extrusion is 180°C, and the screw speed is controlled at 100r / min to obtain the modified polyethylene resin.
[0052] Compared with Example 1, in Comparative Example 4, carbon fiber and nano-titanium dioxide are directly added into the foaming extruder for melt blending.
[0053] The performance of the EPE composite materials prepared in Examples 1-3 and Comparative Examples 1-4 was tested as follows: Tensile strength test: Tested in accordance with GB / T 6344-2008 standard; Elongation at break test: Tested in accordance with GB / T 6344-2008 standard; Tear strength test: Tested in accordance with GB / T 10808-2006 standard; Thermal aging test: After being treated in an aging box at 100°C for 96 hours, the tensile strength retention rate is tested; The test results are shown in Table 1: Table 1 Mechanical properties test results of different groups of composite materials
[0054] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.
Claims
1. A high-strength tear-resistant EPE composite material, characterized in that: The raw materials include the following components in parts by weight: 80-100 parts of modified polyethylene resin, 20-30 parts of polycaprolactone, 15-25 parts of foaming agent, 10-20 parts of carbon fiber composite material, 1-3 parts of zinc stearate and 1-2 parts of antioxidant.
2. The high-strength tear-resistant EPE composite material according to claim 1, characterized in that: The preparation method of the modified polyethylene resin is as follows: polyethylene resin and silane coupling agent KH560 are uniformly mixed, and the mixture is melt-extruded by a screw to obtain the modified polyethylene resin.
3. The high-strength tear-resistant EPE composite material according to claim 2, characterized in that: The mass ratio of polyethylene resin to silane coupling agent KH560 is 100:3-5.
4. The high-strength tear-resistant EPE composite material according to claim 1, characterized in that: The preparation method of the carbon fiber composite material is as follows: S1, dispersing carbon fiber in an ethanol aqueous solution, then adding diallyldiethoxysilane thereto, stirring for 1-3 hours, then filtering, washing, and drying to obtain pretreated carbon fiber; S2, dispersing the pretreated carbon fiber in deionized water, then adding p-hydroxycinnamic acid and initiator persulfate thereto, heating and stirring to react, and after the reaction is completed, filtering, washing, and drying to obtain modified carbon fiber; S3, dispersing the modified carbon fiber in an ethanol solvent, then adding deionized water, ammonia water and tetrabutyl titanate thereto, stirring for 6-12 hours, and after the reaction is completed, filtering, washing and drying to obtain a carbon fiber composite material.
5. The high-strength tear-resistant EPE composite material according to claim 4, characterized in that: In step S1, the mass ratio of carbon fiber to diallyldiethoxysilane is 10-15:1-2.
6. The high-strength tear-resistant EPE composite material according to claim 4, characterized in that: In step S2, the mass ratio of the pretreated carbon fiber, p-hydroxycinnamic acid and persulfate is 10-15:4-8:0.5-1.
7. The high-strength tear-resistant EPE composite material according to claim 4, characterized in that: In step S2, the temperature of the heating and stirring reaction is 60-80° C., and the time of the heating and stirring reaction is 2-4 h.
8. The high-strength tear-resistant EPE composite material according to claim 4, characterized in that: In step S3, the mass ratio of modified carbon fiber, ethanol, deionized water, ammonia water and tetrabutyl titanate is 5-10:150:5-10:10-15:10-20.
9. The high-strength tear-resistant EPE composite material according to claim 1, characterized in that: The foaming agent is selected from butane, and the antioxidant is selected from antioxidant 1010.
10. A method for preparing the high-strength tear-resistant EPE composite material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding modified polyethylene resin, polycaprolactone and carbon fiber composite material into a foaming extruder according to weight parts, melt blending to obtain a mixed material, then adding a foaming agent, zinc stearate and an antioxidant, foaming for 15-20 minutes under the conditions of a temperature of 180-200°C and an inlet pressure of 8-12MPa, and cooling after the foaming is completed to obtain a high-strength tear-resistant EPE composite material.
Citation Information
Patent Citations
Tear-resistant EPE and its preparation method
CN108264679B
Preparation method of titanium-dioxide-modified carbon-fiber-reinforced resin-base composite material
CN105602000A
Tear resistant EPE and preparation method thereof
CN108264679A
High-strength aging-resistant polyethylene composite material for photovoltaic floating bodies and preparation method thereof
CN111253661A
High-strength degradable EPE heat-insulation pearl wool board and processing method
CN113071172A
